Socio Economic Effects of Developed and Under Developing Mega Housing Projects on Rural Area: A Case Study of Rawalpindi and Islamabad - Qayyum, Hira; Sherwani, Rummana; Waheed, Abdul (Annals of Human and Social Sciences, 2022)
Housing is a major concern in all over the world and show the quality of life and living standards. Housing in presence of proper infrastructure can provide a wide range of positive impacts like improved health, safety from hazard, security, privacy and social well-being. Aims of the study is to determine the impacts of developed and under developing mega housing projects on rural areas. The geographic location of the mega housing projects is influencing nearby rural areas directly and indirectly. Indicator based approach is used to understand these impacts of both developed and under developing housing schemes on surrounding rural areas. Eight indicators were shortlisted and recorded on a 5-point Likert scale. The acquired data of 251 respondents, 135 from developed housing schemes and 116 from under developing housing schemes were analyzed statistically using Pearson Chi-Square and weighted mean method. Result shows that out of eight indicators 5 indicators (Education, Health, Market, Social and Economy) have a significant difference between developed and under developing housing schemes impacts on rural areas. Three out of eight indicators (Roads and connectivity, Environment and Gender) have same impact of developed and under developing on rural areas. The study indicates that Education, Health, Market, Social and Economy are affecting the rural areas in a different way than Roads and connectivity, Environment and Gender indicator.